Acción pública local: una alternativa para dotar de agua potable a las colonias de la periferia de Ciudad Juárez, Chihuahua - Córdova Borjórquez, Gustavo (El Colegio de México A.C., 2018)
This paper analyzes the convergence of governmental and non-governmental actors in implementing local public action as an alternative for providing drinking water for neighborhoods without this service in Ciudad Juárez, Chihuahua. To this end, an analysis is conducted of the macrosocial and microindividual dimensions, which makes it possible to observe the scope of the public action that can be carried out by both actors. The paper specifically seeks to explore the endogenously induced component of local public action, its characteristics and evolution over time. The results indicate that there is no convergence among actors since neither the government nor the non-governmental agents studied, in this case, heads of households, have been able to develop joint strategies. There are key elements, both macrosocial and microindividual, to be taken into account, in order to develop a local public action.